Modiolus (Modiolus) nipponicus - Lutaenko, K. A.; Kepel, A. A. (Zenodo, 2017)
Modiolus ( Modiolus ) nipponicus (Oyama, 1950) Рис. 1C–F; 2C Modiolaria semigranata (Reeve, 1858): Yokoyama, 1924, p. 53, pl. 3, fig. 14. (non Reeve, 1858). Volsella traillii (Reeve, 1857): Nomura, Hatai, 1935, p. 7 (non Reeve, 1857). Volsella nipponica Oyama, 1950, p. 1. Volsella ( Volsella ) nipponica Oyama, 1950: Habe, 1951, p. 50; Ichikawa, 1983, p. 523. Volsella agripeta Iredale, 1939: Kuroda, Habe, 1952, p. 35 (non Iredale, 1939). Modiolus nipponicus (Oyama, 1950): Kuroda, 1957. p. 28; Yamamoto, Habe, 1958, p. 8, pl. 4, fig. 11; Kira, 1959, p. 116, pl. 45, fig. 16; Horikoshi, 1960, p. 11; Ito, 1967, p. 65; Habe et al., 1986, p. 27;? Lee, Morton, 1985, p. 59, pl. 4, fig. D; Kim, Choe, 1988, p. 374; Fukuda et al., 1992, p. 83, pl. 27, fig. 446a, b; Huang, 1994, p. 390; Shell of Toyama City…, 1994, p. 47; Kanzaemon Kikuchi’s Shell Collection, 1997, p. 81; Nakaba Tachibana’s Shell Collection, 1999, p. 62; Okutani, 2000, p. 867, pl. 431, fig. 19; Kubota, Koyama, 2002, p. 135; Hylleberg, Kilburn, 2003, p. 144; Valentich-Scott, 2003, p. 268; Qi, 2004, p. 231, pl. 121, fig. D; Wu, 2004, p. 22; Son, Hong, 2005, p. 86 (non fig.); Suzuki et al., 2006, p. 63; Xu, Zhang, 2008, p. 57, fig. 153; Toba, 2009, p. 71, fig. 7 (p. 72); Huber, 2010, p. 123, fig.; Ohgaki, 2010, p. 40; Report…, 2010, p. 15; Takebayashi, Wada, 2010, p. 19; Ohgaki et al., 2011, p. 13; Saijo, Nagashima, 2012, p. 2; Satuito et al., 2013, p. 6; Seo, Tanangonan, 2014, p. 106; Yamamoto, Handa, 2015, p. 156; Itsukushima et al., 2017: p. [6]. Modiolus ( Modiolus ) agripetus (Iredale, 1939): Kuroda et al., 1971, p. 545 (Jap.), 345 (Eng.), pl. 73, fig. 15; Mollusca of Toyama …, 1988, p. 75; Higo et al., 1999, p. 415; Lee, Min, 2002, p. 152; Min et al., 2004, p. 377, fig. 1200; Hong et al., 2004, p. 202; Lutaenko, Noseworthy, 2012, p. 38; Lee, 2013, p. 73, fig. 34 (non Iredale, 1939). Modiolus agripetus (Iredale, 1939): Habe, 1973, p. 15; Yoo, 1976, p. 112, pl. 23, fig. 5; Tan et al., 1980, p. 66, text-fig. (as agripedus ); Lee et al., 1984, p. 123; Kim, ...